“I Have Friends Everywhere”: A Fieldguide for Community Archive Activists - Joseph Sherren; Ronald Padrón (The Political Librarian, 2025)
“I Have Friends Everywhere” is an opinion piece written by Joseph Sherren and Ronald Padrón in light of the massive erasure and displacement of public data under the custodianship of the U.S. government. This piece is a call to arms along with a down to basics recommendation of digital recordkeeping and archiving for community archivist/activists who take it upon themselves to download, describe, and keep safe data and records. We aim to provide concrete steps leading to the protection of public information in light of the U.S. Government's abdication of its responsibility to hold and protect information for the public good.
Keywords: Archives; Activism; Recordkeeping; Archivist/ Activist; Community Archiving; Opinion